Philosophy, identity and political thought in Latin America (Polis (Santiago), 2018)
The Latin-American Philosophy was born with the conflict about what is own and what is alien, that is to say a philosophy that did of its own statute of possibility the content to develop.  Therefore, a thought that far away from the metaphysical and epistemologic canons of  west europe, has tried since its beginnings to answer the two fundamental questions for our region ¿What we are? and ¿What can we be in the world order?  With all the political and identity load that these questions carry behind them.  The present article intends to foresee that ideology since the emancipators and the positivists of the end of the 19th century up to the revolutionary philosophy of the sixties.
Keywords: Latin-American philosophy; emancipating; political thought; positivists